Soluble Domain 1 of Platelet–Endothelial Cell Adhesion Molecule (PECAM) Is Sufficient to Block Transendothelial Migration In Vitro and In Vivo - Liao, Fang (The Rockefeller University Press, 1997)
The inflammatory response involves sequential adhesive interactions between cell adhesion molecules of leukocytes and the endothelium. Unlike the several adhesive steps that precede it, transendothelial migration (diapedesis), the step in which leukocytes migrate between apposed endothelial cells, appears to involve primarily one adhesion molecule, platelet–endothelial cell adhesion molecule (PECAM, CD31). Therefore, we have focused on PECAM as a target for antiinflammatory therapy. We demonstrate that soluble chimeras made of the entire extracellular portion of PECAM, or of only the first immunoglobulin domain of PECAM, fused to the Fc portion of IgG, block diapedesis in vitro and in vivo. Furthermore, the truncated form of the PECAM-IgG chimera does not bind stably to its cellular ligand. This raises the possibility of selective anti-PECAM therapies that would not have the untoward opsonic or cell-activating properties of antibodies directed against PECAM.